2015
DOI: 10.1299/mej.14-00402
|View full text |Cite
|
Sign up to set email alerts
|

NO formation/reduction mechanisms of ammonia/air premixed flames at various equivalence ratios and pressures

Abstract: Ammonia is a carbon-free fuel and its application to internal combustion engines is expected. However, few studies on ammonia flames, especially at high pressures, have been carried out because ammonia has not been considered to be a fuel owing to its lower combustion intensity. Most of NOx, which is formed by ammonia combustion, is considered to be the fuel NOx. The objectives of this study were to investigate the fundamental characteristics of NOx experimentally, such as NO emission and chemiluminescence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
80
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(97 citation statements)
references
References 21 publications
9
80
0
2
Order By: Relevance
“…This reduction in the production of HNO is consistent with the reduction of NO emission observed by Hayakawa (2015). The two main contributors to heat release, which are NH3+OH⇋NH2+H2O and NH2+OH⇋NH+H2O, are only weakly affected by a rise in pressure, which is consistent with a lower decrease in NH3 flame burning velocity with pressure, P -0.20 , than for CH4.…”
Section: Discussion On Chemistrysupporting
confidence: 85%
See 1 more Smart Citation
“…This reduction in the production of HNO is consistent with the reduction of NO emission observed by Hayakawa (2015). The two main contributors to heat release, which are NH3+OH⇋NH2+H2O and NH2+OH⇋NH+H2O, are only weakly affected by a rise in pressure, which is consistent with a lower decrease in NH3 flame burning velocity with pressure, P -0.20 , than for CH4.…”
Section: Discussion On Chemistrysupporting
confidence: 85%
“…Results are plotted in Colson, Hayakawa, Kudo and Kobayashi, Journal of Thermal Science and Technology, Vol.11, No.3 (2016) It is initially noted that the extinction stretch rate of NH3 flame (100 s -1 ) is around 20 times lower than that of CH4 flame (2000 s -1 ) at 1 atm. This difference might be understood given the large difference in their laminar burning velocities, around 7 cm/s for NH3 flame and around 37 cm/s for CH4 flame for stoichiometric conditions (Hayakawa et al, 2015). From Fig.…”
Section: Extinction Stretch Ratementioning
confidence: 91%
“…NH 3 has recently been regarded as a renewable and carbon-free energy source due to its high energy density, 13) but it has problems including high ignition temperature and N 2 O/NO x production, in comparison with fossil fuels. Previously, we proposed novel catalytic NH 3 combustion systems that enable low ignition temperatures as well as negligible N 2 O/NO x emissions, 14)16) and reported that the NH 3 combustion activity of metal oxides increases with a decrease in their metaloxygen bond energy.…”
mentioning
confidence: 99%
“…近年,欧米をはじめとする諸外国を中心にアンモニアを代替燃料とするための研究が行われている (Zamfirescu and Dincer, 2008, Takizawa et al, 2008, Ronny, 1988, Kumar and Meyer, 2013, Duynslaegher et al, 2009, Duynslaegher et al, 2010, Pfahl et al, 2000, Li et al, 2014, Hayakawa et al, 2015a, Hayakawa et al, 2015b, Ichikawa et al, 2015, 武石他, 2015, 武石他, 2016, 小林, 早川, 2016, 小池他, 2016, 武石他, 2017 (水谷, 矢野, 1978, Chung and Lee, 1991, Takahashi and Schmoll, 1990, 小谷他, 2004, Otakeyama et al, 2009 …”
Section: 緒 言unclassified